Complete mitochondrial genome of the freshwater monogonont rotifer Brachionus calyciflorus (Rotifera, Brachionidae). Issue 2 (3rd July 2019) - Choi, Beom-Soon; Lee, Young Hwan; Hagiwara, Atsushi; Lee, Jae-Seong
Abstract: The two complete mitochondrial genomes were sequenced from the Netherlands strain of the freshwater monogonont rotifer Brachionus calyciflorus . The mitochondrial genome sequences were 27, 698 bp and 9, 906 bp in size, respectively. The gene order and contents of the two B. calyciflorus strains were mostly identical to one another, except for the additional identification and translocation of several tRNAs in mitochondrial DNA I and II. Of 13 protein-coding genes (PCGs), three genes ( ND1, ND5, and ND3 ) had incomplete stop codons. Furthermore, the start codon of ND2, CO2, and CO3 and ND4 genes was ATT, GTG, and ATA, respectively, while the start codon of other PCGs was ATG. The base composition of 13 PCGs of B. calyciflorus (the Netherlands strain) mitogenome showed 31.1% for A, 37.6% for T, 16.5% for C, and 14.8% for G, respectively.